2019
DOI: 10.1002/anie.201909831
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Electrochemical Ammonia Synthesis in Molten LiCl–KCl Eutectics

Abstract: Molten LiCl and related eutectic electrolytes are known to permit direct electrochemical reduction of N2 to N3− with high efficiency. It had been proposed that this could be coupled with H2 oxidation in an electrolytic cell to produce NH3 at ambient pressure. Here, this proposal is tested in a LiCl–KCl–Li3N cell and is found not to be the case, as the previous assumption of the direct electrochemical oxidation of N3− to NH3 is grossly over‐simplified. We find that Li3N added to the molten electrolyte promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
0
19
1
Order By: Relevance
“…Detailed investigation into the electrochemical mechanism has revealed the existence of a number of rapid non-electrochemical reactions of N 3− with H 2 to form NH 3 along with NH 2− and NH 2 − , which are shown to be electrochemically active by cyclic voltammetry. 62 An alternative strategy was recently demonstrated in which Li metal was used to reduce N 2 . 63 So far, several thousand electro-and photocatalysts were screened worldwide in the development of non-thermal NH 3 synthesis.…”
Section: ■ H 2 Production By Thermal/photochemical/electrochemical Meansmentioning
confidence: 89%
See 1 more Smart Citation
“…Detailed investigation into the electrochemical mechanism has revealed the existence of a number of rapid non-electrochemical reactions of N 3− with H 2 to form NH 3 along with NH 2− and NH 2 − , which are shown to be electrochemically active by cyclic voltammetry. 62 An alternative strategy was recently demonstrated in which Li metal was used to reduce N 2 . 63 So far, several thousand electro-and photocatalysts were screened worldwide in the development of non-thermal NH 3 synthesis.…”
Section: ■ H 2 Production By Thermal/photochemical/electrochemical Meansmentioning
confidence: 89%
“…However, we have recently demonstrated that the previous assumption of a direct electrochemical reaction of N 2 and H 2 in molten LiCl–KCl to form NH 3 with high efficiency is not correct. Detailed investigation into the electrochemical mechanism has revealed the existence of a number of rapid non-electrochemical reactions of N 3– with H 2 to form NH 3 along with NH 2– and NH 2 – , which are shown to be electrochemically active by cyclic voltammetry . An alternative strategy was recently demonstrated in which Li metal was used to reduce N 2 .…”
Section: Nh3 Production By Thermal/photochemical/electrochemical Meansmentioning
confidence: 99%
“…The nitrogen generation section of the process was adapted from Gomez et al 22 [Colour figure can be viewed at wileyonlinelibrary.com] via electrolyte variation. We keep in mind current experimental rates 24 for ammonia formation up to 10 −8 mol s −1 cm −2 compared to the DOE target of 90% with 9.33 × 10 −7 mol s −1 cm −2 . This brings to bear that higher FE presently comes at the expense of ammonia formation rate.…”
Section: Process Simulationmentioning
confidence: 99%
“…19,20 It was reported that the electrosynthesis of NH 3 from N 2 and H 2 using molten chloride electrolytes at elevated temperatures could be faster ($10 À8 mol , cm À2 s À1 ), 21 but the result may be flawed, according to a recent investigation. 22 The claim of NH 3 synthesis from N 2 of only a very small amount should be carefully verified by 15 N tracing to avoid false positives. 23,24 Recently, it was reported that an indirect electrochemical NH 3 synthesis, based on electrolyzing molten LiOH into Li, O 2 , and H 2 O, and using Li to fix N 2 into Li 3 N, shows potential advantages of both high speed ($10 À7 mol , cm À2 s À1 ) and coulombic efficiency (88.5%).…”
Section: Introductionmentioning
confidence: 99%